Regulated and polarized PtdIns(3,4,5)P3 accumulation is essential for apical membrane morphogenesis in photoreceptor epithelial cells. - Pinal, N; Goberdhan, D; Collinson, L; Fujita, Y; Cox, I; Wilson, C; Pichaud, F (2006)
BACKGROUND: In a specialized epithelial cell such as the Drosophila photoreceptor, a conserved set of proteins is essential for the establishment of polarity, its maintenance, or both--in Drosophila, these proteins include the apical factors Bazooka, D-atypical protein kinase C, and D-Par6 together with D-Ecadherin. However, little is known about the mechanisms by which such apical factors might regulate the differentiation of the apical membrane into functional domains such as an apical-most stack of microvilli or more lateral sub-apical membrane. RESULTS: We show that in photoreceptors Bazooka (D-Par3) recruits the tumor suppressor lipid phosphatase PTEN to developing cell-cell junctions (Zonula Adherens, za). za-localized PTEN controls the spatially restricted accumulation of optimum levels of the lipid PtdIns(3,4,5)P3 within the apical membrane domain. This in turn finely tunes activation of Akt1, a process essential for proper morphogenesis of the light-gathering organelle, consisting of a stack of F-actin rich microvilli within the apical membrane. CONCLUSIONS: Spatially localized PtdIns(3,4,5)P3 mediates directional sensing during neutrophil and Dictyostelium chemotaxis. We conclude that a conserved mechanism also operates during photoreceptor epithelial cell morphogenesis in order to achieve normal differentiation of the apical membrane.